1989
DOI: 10.1139/y89-157
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endogenous calcium transport inhibitor from heart muscle on the active calcium uptake and passive calcium release properties of sarcoplasmic reticulum

Abstract: In the present study, the effects of the cytosolic Ca2+ transport inhibitor on ATP-dependent Ca2+ uptake by, and unidirectional passive Ca2+ release from, sarcoplasmic reticulum enriched membrane vesicles were examined in parallel experiments to determine whether inhibitor-mediated enhancement in Ca2+ efflux contributes to inhibition of net Ca2+ uptake. When assays were performed at pH 6.8 in the presence of oxalate, low concentrations (less than 100 micrograms/mL) of the inhibitor caused substantial inhibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In spite of the findings by Narayanan et al [1,3,7,21, 23] and Chiesi et al [2,4], the physiological role of the antagonist protein still remains to be established. However, Chiesi et al pointed out that the antagonist protein is located at the A/I junction in muscle, where transverse tubules reside in mammalian striated muscular cells [24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of the findings by Narayanan et al [1,3,7,21, 23] and Chiesi et al [2,4], the physiological role of the antagonist protein still remains to be established. However, Chiesi et al pointed out that the antagonist protein is located at the A/I junction in muscle, where transverse tubules reside in mammalian striated muscular cells [24].…”
Section: Resultsmentioning
confidence: 99%
“…[2,4] later corroborated the occurrence of such proteins in the cardiac cytosol of guinea pigs. Narayanan et al [3] reported that the inhibitory protein did not disturb the Ca2+ release process from the SR in the presence of oxalate, whereas Chiesi and Schwaller [2] showed accelerated Ca2+ release from passively Ca2+-loaded SR. Narayanan et al [21] later reported two aspects of the inhibitor, activation of Ca2+ uptake at pH 6.8 and inhibition at pH 7.4. Chiesi et al [2,4] identified the inhibitor protein as an isoform of actin, a major component of contractile proteins, and the antagonist protein as f3-actinin, now called muscle albumin.…”
Section: Resultsmentioning
confidence: 99%